2017
DOI: 10.21475/ajcs.17.11.12.pne523
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, pollen behavior and propagation of five selected Hibiscus hybrids (Hibiscus rosa-sinensis Linn.)

Abstract: Breeding and characterization of Hibiscus hybrids in the Philippines was conducted to improve the local varieties for them to have unique flower colors and forms by introducing genes from foreign varieties. The Hibiscus hybrids are important ornamental genetic materials being used to honor outstanding Filipina achievers. The study aimed to characterize 5 new selected hybrids, test their pollen fertility and evaluate their graft compatibility with 2 known rootstock varieties. The important characteristics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Daya tarik Hibiscus rosa-sinensis L. khususnya dalam hal keanekaragaman struktur bunga yang meliputi warna, bentuk dan ukuran menyebabkan adanya upaya untuk menjadikan tanaman tersebut lebih bervariasi diantaranya melalui proses hibridisasi atau persilangan (Pascual et al, 2017;Abirami, 2018;Mauhay et al, 2020). Analisis keanekaragaman atau polimorfisme tingkat genetik menunjukkan bahwa variasi bunga Hibiscus rosa-sinensis L. cukup tinggi (Mercuri et al, 2010).…”
Section: Pendahuluanunclassified
“…Daya tarik Hibiscus rosa-sinensis L. khususnya dalam hal keanekaragaman struktur bunga yang meliputi warna, bentuk dan ukuran menyebabkan adanya upaya untuk menjadikan tanaman tersebut lebih bervariasi diantaranya melalui proses hibridisasi atau persilangan (Pascual et al, 2017;Abirami, 2018;Mauhay et al, 2020). Analisis keanekaragaman atau polimorfisme tingkat genetik menunjukkan bahwa variasi bunga Hibiscus rosa-sinensis L. cukup tinggi (Mercuri et al, 2010).…”
Section: Pendahuluanunclassified
“…Some sources suggest that fruits can possibly form as 3 cm long capsules but very rarely. Although H. rosa-sinensis appear in variety of different corolla sizes, shapes and colors (Figure 1) such as yellow, orange, pink, and white [15,16,17], the wild type for this plant remains as bright red flowers that grow in single forms [18] Phytochemistry: Each part of H. rosa sinensis contains a wide range of compounds (Figure 2). It was reported that phlobatannins, glycosides, saponins, flavonoids, terpenoids including other compounds such as thiamine, riboflavin and niacin are present in leaves, flowers, stem and roots [19].…”
Section: Introductionmentioning
confidence: 99%